Using scenarios to test the appropriateness of pharmacist prescribing in asthma management - Hanna T; Bajorek B; LeMay K; Armour CL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To explore the potential for community pharmacist prescribing in terms of usefulness, pharmacists' confidence, and appropriateness, in the context of asthma management. Methods: Twenty community pharmacists were recruited using convenience sampling from a group of trained practitioners who had already delivered asthma services. These pharmacists were asked to complete a scenario-based questionnaire (9 scenarios) modelled on information from real patients. Pharmacist interventions were independently reviewed and rated on their appropriateness according to the Respiratory Therapeutic Guidelines (TG) by three expert researchers. Results: In seven of nine scenarios (78%), the most common prescribing intervention made by pharmacists agreed with TG recommendations. Although the prescribing intervention was appropriate in the majority of cases, the execution of such interventions was not in line with guidelines (i.e. dosage or frequency) in the majority of scenarios. Due to this, only 47% (76/162) of the interventions overall were considered appropriate. However, pharmacists were deemed to be often following common clinical practice for asthma prescribing. Therefore 81% (132/162) of prescribing interventions were consistent with clinical practice, which is often not guideline driven, indicating a need for specific training in prescribing according to guidelines. Pharmacists reported that they were confident in making prescribing interventions and that this would be very useful in their management of the patients in the scenarios. Conclusion: Community pharmacists may be able to prescribe asthma medications appropriately to help achieve good outcomes for their patients. However, further training in the guidelines for prescribing are required if pharmacists are to support asthma management in this way.